2021
DOI: 10.1038/s41416-021-01474-y
|View full text |Cite
|
Sign up to set email alerts
|

Highlights from ASCO-GI 2021 from EORTC Gastrointestinal tract cancer group

Abstract: Last year the field of immunotherapy was finally introduced to GI oncology, with several changes in clinical practice such as advanced hepatocellular carcinoma or metastatic colorectal MSI-H. At the virtual ASCO-GI symposium 2021, several large trial results have been reported, some leading to a change of practice. Furthermore, during ASCO-GI 2021, results from early phase trials have been presented, some with potential important implications for future treatments. We provide here an overview of these importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…In addition, total neoadjuvant therapy has also received considerable attention. The results of the NRG-GI002 study showed that pembrolizumab added to CRT as part of total neoadjuvant therapy was safe, but it failed to improve the neoadjuvant rectal score and needed further exploration [88,89].…”
Section: Publication Bias and Sensitivity Analysismentioning
confidence: 99%
“…In addition, total neoadjuvant therapy has also received considerable attention. The results of the NRG-GI002 study showed that pembrolizumab added to CRT as part of total neoadjuvant therapy was safe, but it failed to improve the neoadjuvant rectal score and needed further exploration [88,89].…”
Section: Publication Bias and Sensitivity Analysismentioning
confidence: 99%
“…Taken together, these conditions are responsible for poor prognosis in these tumors. Thus, despite current available knowledge on molecular determinants involved in the initiation and progression of cancer [ 4 ], there is an urgent clinical need to further improve our biological knowledge of gastrointestinal evolutionary processes toward increased dysregulation, heterogeneity, and the escape from immunosurveillance as well as from pharmacological treatment control [ 5 , 6 ].…”
mentioning
confidence: 99%